The Ultimate Studio One Pro Book : A step-by-step guide to recording, editing, mixing, and mastering professional-quality music /: A step-by-step guide to recording, editing, mixing, and mastering professional-quality music. (2023) - Somunkiran, Doruk
No abstract available